The Responsibility of a Sea Freight Transport Management Services Company for Damage to Goods in a Third-Party Logistics Agreement - Ramadhani, A. Zainur Rasyidi; Vandawati, Zahry; Subagyono, Bambang Sugeng Ariadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze the limits and forms of accountability carried out by Freight Forwarding companies which are based on TPL agreements. This research is normative legal research with a conceptual, case and statutory approach. The research results confirm that Freight Forwarding's liability limits only cover damage and loss of goods resulting from errors and/or negligence from management and logistics management aspects which are direct losses. In connection with losses that are consequential or indirect, responsibility cannot be held. Liability is excluded in the event of force majeure or losses caused by the carrier. The form of accountability that must be given by Freight Forwarding regarding its mistakes is that first Freight Forwarding must be able to prove that it is not guilty according to the principle of presumption of liability. However, if Freight Forwarding cannot prove that it is not at fault then the form of liability that Freight Forwarding must provide is compensation as specified in the TPL agreement.